Gen-Gen yang Berperan dalam Mekanisme Epilepsi Resisten terhadap Obat - Shinta Nurhaliza; Roro Rukmi Windi Perdani; Intan Kusumaningtyas; Rasmi Zakiah Oktarlina (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Drug-resistant epilepsy represents a major clinical challenge due to its complex and multifactorial biological mechanisms. This condition is not solely driven by inadequate pharmacological efficacy but is strongly influenced by genetic alterations affecting drug transport, neuronal excitability, and neuroinflammatory regulation. Genes encoding drug transporters such as ABCB1 and ABCC2 limit antiepileptic drug penetration across the blood–brain barrier, reducing therapeutic concentrations within epileptogenic regions. Meanwhile, mutations in sodium channel genes, particularly SCN1A, SCN2A, and SCN8A, disrupt neuronal excitability by altering action potential dynamics and synaptic balance. In parallel, neuroinflammatory genes including IL1B, TNF, and TLR4 promote chronic inflammatory responses that sustain epileptogenesis and further reduce drug responsiveness. The interaction among these genetic pathways creates a self-reinforcing pathological network that underlies persistent seizure activity despite optimal treatment. Understanding these molecular mechanisms highlights the necessity of precision-based approaches, including pharmacogenetic screening and targeted adjunctive therapies, to improve clinical outcomes in patients with drug-resistant epilepsy.